Multiple cystic pulmonary chondroid hamartomas colonized by Aspergillus species: Report of a case - Ozyurtkan, Mehmet Oguzhan; Dagli, Adile Ferda; Cakmak, Muharrem; Balci, Akin Eraslan (Springer, 2011)
Pulmonary hamartoma is the most common benign neoplasm of the lung, but the cystic form is very rare. This report presents the case of a 31-year-old woman with two cystic pulmonary lesions. She was radiologically and clinically diagnosed to have multiple ruptured hydatid cysts, and underwent a thoracotomy. The pathological investigation revealed that these lesions were cystic chondroid hamartomas, and one of the cysts was colonized by Aspergillus. Multilocular pulmonary cystic hamartomas are exceptionally rare and should be differentiated from other cystic pulmonary lesions. This is the first case of cystic pulmonary hamartomas colonized by Aspergillus species.
Keywords: Aspergillus; Hamartoma; Thoracotomy